Ultrastructure of the anterior organ and posterior funnel-shaped canal of Gyrocotyle urna Wagener, 1852 (Cestoda: Gyrocotylidea) - Poddubnaya, Larisa G; Kuchta, Roman; Bristow, Glenn A; Scholz, Tomas (Folia parasitologica, 2015)
Using scanning and transmission electron microscopy, ultrastructure of the anterior organ and posterior funnel-shaped canal of Gyrocotyle urna Wagener, 1852 (Cestoda: Gyrocotylidea) from ratfish, Chimaera monstrosa (Holocephali), was studied for the first time. The proper anterior organ is localised at a short distance (about 170 µm) from an apical pore surrounded by a receptor field, whereas its distal end is marked by a muscular sphincter. The tegumental surface of this organ is covered with short filitriches of irregular length; large area of muscle layers traverse beneath the tegumental layer. The funnel-shaped canal of G. urna (2.5-3.0 mm long) is a specialised, muscular part of the posterior attachment organ; it opens on the rounded elevation on the dorsal body surface. The tegumental layer bears conical sclerite-like structures (up to 1.5 µm long). It produces electron-dense bodies that are transported into a canal lumen and surrounded thick muscle area mixed with numerous nerve fibres. The present ultrastructural study of G. urna indicates that gyrocotylideans share some ultrastructural characters of the anterior organ with spathebothriidean cestodes with a single anterior attachment sucker-like organ. In contrast, the unique posterior rosette attachment organ with funnel-shaped canal of the Gyrocotylidea resembles the haptor of polyopisthocotylean monogeneans in its position at the posterior end of the body and presumed origin. The above-mentioned features add more clarity to support the basal position of the Gyrocotylidea Poche, 1926 among cestodes. In addition, they also indicate a possible relationship of gyrocotylidean ancestors with monogeneans.
Keywords: transmission electron microscopy; scanning electron microscopy; phylogeny; ultrastructural characters; basal cestodes